2020
DOI: 10.5194/acp-20-2099-2020
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of pollen data in source maps is vital for pollen dispersion models

Abstract: Abstract. Information about distribution of pollen sources, i.e. their presence and abundance in a specific region, is important, especially when atmospheric transport models are applied to forecast pollen concentrations. The goal of this study is to evaluate three pollen source maps using an atmospheric transport model and study the effect on the model results by combining these source maps with pollen data. Here we evaluate three maps for the birch taxon: (1) a map derived by combining a land cover d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
(95 reference statements)
2
24
1
Order By: Relevance
“…We found that the grass SPIn varies from year to year and from station to station by a factor of 2 to 4. The SPIn has been used in atmospheric models to take into account the seasonal magnitude of pollen emission and its spatial and interannual variation for different pollen types (35,36). Therefore, our findings have the potential to be used in atmospheric dispersion models for Northwest Europe or larger regions throughout the world where sufficient robust pollen data are available.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the grass SPIn varies from year to year and from station to station by a factor of 2 to 4. The SPIn has been used in atmospheric models to take into account the seasonal magnitude of pollen emission and its spatial and interannual variation for different pollen types (35,36). Therefore, our findings have the potential to be used in atmospheric dispersion models for Northwest Europe or larger regions throughout the world where sufficient robust pollen data are available.…”
Section: Discussionmentioning
confidence: 98%
“…Validation of chemical transport models for birch pollen over Europe has been done by Sofiev et al (2015) and Kurganskiy et al (2020). Sofiev et al (2015) presented the results for six individual models and for the ensemble approach based on comparison of the modelled concentrations with stations located in 11 European countries for the year 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficient (mean for all stations) for individual models varied from 0.28 to 0.41, while the mean from all models was equal to 0.38. Kurganskiy et al (2020) ran the Enviro-HIRLAM model over Europe and validated the results against stations located in Finland, Russia, and Denmark for the year 2006. They ran three types of simulations: (1) a standard run, (2) a run that includes a correction for 2-m air temperature based on observational data, and (3) a simulation that includes both the correction for temperature and a grid-based scaling factor for pollen emission based on pollen observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations